EVALUATION OF THE MOTIVATIONS OF WOMEN'S ENTERPRISE COOPERATIVES IN MARKETING PROCESSES FOR EXPO/FAIR ORGANIZATIONS: HATAY EXPO2021 EXAMPLE (Third Sector Social Economic Review, 2024)
Expo organizations involve a significant process for cities and all stakeholders. This study evaluates the motivations and interactions of women's cooperatives with Expo organizations through the case of Hatay Expo 2021. The aim of the research is to determine the expectations of women's cooperatives during the Expo process and the impact of the Expo on their marketing strategies. For this purpose, both qualitative and quantitative data collection methods were used. Focus group interviews and face-to-face interviews were conducted for qualitative analysis, while quantitative data were obtained through a web-based survey. The results of the study show that the potential of Hatay province was utilized during the Expo, but the participants' expectations were not fully met. Recommendations are provided to make future Expo organizations more effective and to better manage the expectations of women's cooperatives.
Keywords: Women's Cooperatives; Marketing Strategies; Hatay; Expo 2021